Treatment of a patient suffering from posttraumatic painful neuromas formed at the bilateral digital nerves of the left middle finger using two neurovascular island flaps. (March 2019) - Iemura, Shunki; Kakinoki, Ryosuke; Ohtani, Kazuhiro; Hashimoto, Kazuhiko; Nakamura, Fumihisa; Tanaka, Hiroki; Akagi, Masao
Abstract: Hand surgeons often encounter painful posttraumatic neuromas in daily practice and the treatment of these neuromas is still challenging for them, because of the tendency of recurrence. 1, 2 The patient injured his left middle finger and was treated by amputation in a previous hospital. After this operation, the patient started to feel pain at the fingertip and complained of severe electric radiating pain when the radial and ulnar ends of the finger were touched. We treated painful neuromas formed on both palmar digital nerve stumps using a reverse pedicle island flap containing subcutaneous nerves, which were connected to the nerve stumps after removal of the neuromas of the finger. This maneuver relieved the finger pain completely. Removal of finger digital nerve neuromas, connecting the nerve stumps to the subcutaneous nerves included in a skin island flap and, covering the neurorrhaphy sites with the flap may have reduced the chance of the recurrence of neuromas and resulted in restoration of considerable function of the hand.